2015
DOI: 10.1111/gcb.12861
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming and agricultural stressors interact to determine stream macroinvertebrate community dynamics

Abstract: Global climate change is likely to modify the ecological consequences of currently acting stressors, but potentially important interactions between climate warming and land-use related stressors remain largely unknown. Agriculture affects streams and rivers worldwide, including via nutrient enrichment and increased fine sediment input. We manipulated nutrients (simulating agricultural run-off) and deposited fine sediment (simulating agricultural erosion) (two levels each) and water temperature (eight levels, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
102
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 58 publications
16
102
2
Order By: Relevance
“…Many headwater rivers are increasingly affected by sedimentation, including those draining peatland catchments, yet experimental studies examining the effect of organic sediment influx on populations, community structure, and functional processes in these river ecosystems remain scarce (Piggott, Lange, Townsend, & Matthaei, ; Piggott et al, ). Our experiment in two peatland rivers revealed that organic sediment influx can have immediate impacts on river water quality and across different levels of biological organisation (macroinvertebrate behavioural drift and whole river metabolism).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many headwater rivers are increasingly affected by sedimentation, including those draining peatland catchments, yet experimental studies examining the effect of organic sediment influx on populations, community structure, and functional processes in these river ecosystems remain scarce (Piggott, Lange, Townsend, & Matthaei, ; Piggott et al, ). Our experiment in two peatland rivers revealed that organic sediment influx can have immediate impacts on river water quality and across different levels of biological organisation (macroinvertebrate behavioural drift and whole river metabolism).…”
Section: Discussionmentioning
confidence: 99%
“…Sedimentation is a major cause of ecological degradation in freshwater ecosystems, with artificially enhanced delivery and retention of fine sediments in rivers and lakes now a significant global problem (Dudgeon et al, ; Larsen & Ormerod, ; Piggott, Townsend, & Matthaei, ; Wood & Armitage, ). A range of policy mechanisms related to the protection of the water environment and wildlife require a better understanding of the scale, nature, and mechanisms of impact so that informed management strategies can be developed and implemented.…”
Section: Introductionmentioning
confidence: 99%
“…In the former, it will reduce water temperature and increase the DO concentration. Thus, multiple stressors and climate change might change the prediction level of river water temperature and DO concentration in an agricultural dominated catchment [63]. However, in our case, we considered the conventional agricultural practices only in the study area and their impact are not considered in our scope of studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, total aquatic insect emergence biomass was not influenced by warming, and thus caused an average larger individuals emerging from warm waterbodies [127]. Conversely, another study showed that only the emerging Chironomidae adults were larger with raised temperature, while the emergence of both medium and large-sized insects were decreased, moreover, rising temperature decreased time to emergence [128]. Warming also increased 38% biomass of overall insect emergence, and advanced the spring pulses of aquatic emergence, and this effect was stronger in the presence of fish [129].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 95%